Experimental investigations of input shaping techniques for double pendulum type overhead crane (DPTOC) system - Mohd Nor Azlan, Zohari (2010)
These project present experimental investigations of input shaping techniques for double pendulum type overhead crane (DPTOC) system. An unshaped bang-bang input force is used to determine the characteristic parameters of the system for design and evaluation of the input shaping control techniques. The positive input shapers with the derivative effects respectively are designed based on the properties of the system. Experimental of the response DPTOC system to shaped input is presented in time and frequency domain. The performance of this project is examined in terms of sway angle reduction and time response specification. Finally comparative assessment of the proposed techniques is presented